2004
DOI: 10.1002/aic.10110
|View full text |Cite
|
Sign up to set email alerts
|

Processing of steel rinse waters through coextraction and selective stripping

Abstract: Recovery of iron(III),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…However, the authors have not mentioned metal ion co-extraction and have not proposed management of the metal salts. Another solvating extractant, Cyanex 923 (a mixture of phosphine oxides) can be successfully applied to recover Fe(III), HNO 3 , and HF with high efficiency [58]. Coextraction (E Fe(III) = 90.6%, E HNO3 = 80.3%, E HF = 85.7%) and selective stripping of iron(III), HNO 3 , and HF with water prove that this method is suitable for SPS processing.…”
Section: Classical and Membrane Based Solvent Extractionmentioning
confidence: 97%
“…However, the authors have not mentioned metal ion co-extraction and have not proposed management of the metal salts. Another solvating extractant, Cyanex 923 (a mixture of phosphine oxides) can be successfully applied to recover Fe(III), HNO 3 , and HF with high efficiency [58]. Coextraction (E Fe(III) = 90.6%, E HNO3 = 80.3%, E HF = 85.7%) and selective stripping of iron(III), HNO 3 , and HF with water prove that this method is suitable for SPS processing.…”
Section: Classical and Membrane Based Solvent Extractionmentioning
confidence: 97%
“…Although neutralization of these waters with lime commonly occurs prior to its discharge, more stringent legislation regarding the discharge of nitrates and other pollutants has led to investigations into the use of more advanced and environmentally friendly techniques for the treatment of these rinse waters. One of the proposed methods combined the use of a membrane (filtering, reverse osmosis, electrodyalisis) and ion exchange technologies [16,17] though the use of liquid-liquid extraction [18], and other technologies [19] have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…It has been used in the extraction of a wide range of metals, including rare earth elements (REEs), transition metals, and precious metals. [26][27][28][29][30][31] In general, extraction of metals by C923 is stronger than extraction by TBP, either for extraction by TBP or C923 alone, 26,32,33 or in combination with another extractant for synergic solvent extraction. 34,35 Recently, it was found that C923 and ciency through the same ion-pair extraction mechanism as the TBP/FeCl 3 (or IL) systems.…”
Section: Introductionmentioning
confidence: 99%
“…Cyanex 923 (C923, a commercial mixture of trialkyl phosphine oxides with mainly n ‐hexyl and n ‐octyl, shown in Figure 1) is a popular commercial neutral extractant that is similar to TBP. It has been used in the extraction of a wide range of metals, including rare earth elements (REEs), transition metals, and precious metals 26‐31 . In general, extraction of metals by C923 is stronger than extraction by TBP, either for extraction by TBP or C923 alone, 26,32,33 or in combination with another extractant for synergic solvent extraction 34,35 .…”
Section: Introductionmentioning
confidence: 99%